2013
DOI: 10.1002/swe.20100
|View full text |Cite
|
Sign up to set email alerts
|

NAIRAS aircraft radiation model development, dose climatology, and initial validation

Abstract: [1] The Nowcast of Atmospheric Ionizing Radiation for Aviation Safety (NAIRAS) is a real-time, global, physics-based model used to assess radiation exposure to commercial aircrews and passengers. The model is a free-running physics-based model in the sense that there are no adjustment factors applied to nudge the model into agreement with measurements. The model predicts dosimetric quantities in the atmosphere from both galactic cosmic rays (GCR) and solar energetic particles, including the response of the geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 77 publications
3
113
0
Order By: Relevance
“…The difference between the effective dose E and the ambient dose equivalent H*(10) is shown in Figure A.3. One can see that the H*(10) is a conservative approach for the exposure in a low rigidity cut-off regions, while the effective dose is a conservative approach above some 5 GV in accord with a recent study (Mertens et al 2013). Moreover, our model computations demonstrate better agreement with the reference data (Figs.…”
Section: Exposure Due To Gcr and Comparison Of The Model With Referensupporting
confidence: 89%
See 3 more Smart Citations
“…The difference between the effective dose E and the ambient dose equivalent H*(10) is shown in Figure A.3. One can see that the H*(10) is a conservative approach for the exposure in a low rigidity cut-off regions, while the effective dose is a conservative approach above some 5 GV in accord with a recent study (Mertens et al 2013). Moreover, our model computations demonstrate better agreement with the reference data (Figs.…”
Section: Exposure Due To Gcr and Comparison Of The Model With Referensupporting
confidence: 89%
“…In general it slightly overestimates the effective dose. However, it is not a conservative estimate for cosmic radiation exposure at aviation altitudes according to Mertens et al (2013) and the work presented here, specifically in high rigidity regions. Nevertheless, it is regarded as an acceptable approximation for effective dose at aircraft altitudes Mertens et al 2013).…”
Section: Definition Of the Dose Ratementioning
confidence: 68%
See 2 more Smart Citations
“…It was demonstrated that the aircrew exposure can be estimated on the basis of a full simulation of the atmospheric cascade (Ferrari et al, 2001;Roesler et al, 2002). Several models have been proposed, aiming to estimate the radiation dose rate (effective and/or ambient dose equivalent) at flight altitudes (Schraube et al, 2000;Ferrari et al, 2001;Roesler et al, 2002;Lewis et al, 2005;Sato et al, 2008;Matthiä et al, 2008;Mertens et al, 2013;. In this study, we employed a recently proposed numerical model for computation of effective and/or ambient dose equivalent at flight altitudes, the details are given elsewhere .…”
Section: Assessment Of Spectral and Angular Constraints Of Sub-gle Pamentioning
confidence: 99%